New onset diabetes after nivolumab treatment. (29th January 2018) - Capitao, Ricardo; Bello, Carlos; Fonseca, Ricardo; Saraiva, Catarina
Abstract : The authors describe a case of a life-threatening diabetic emergency 25 days after initiation of nivolumab (3 mg/kg) for stage 4 lung adenocarcinoma. She was admitted to the emergency department, with hyperglycaemia-related signs and symptoms, such as polyuria, polydipsia, weight loss, confusion, asthenia, dehydration, hypotension and Kussmaul respiratory pattern. Her body mass index was 21.9 kg/m 2 and she did not show acanthosis nigricans. Arterial blood gas determination revealed high anion gap metabolic acidaemia and blood tests showed hyperglycaemia (1060 mg/dL), hyperketonaemia (beta-hydroxybutyrate: 6.6 mmol/dL), elevated total serum osmolality (389 mOsm/kg), low serum and urinary C-peptide and positive antiglutamic acid decarboxylase antibodies. Since nivolumab was initiated a few days before, and due to its known immune-mediated endocrine adverse events, we assumed the diagnosis of new onset immune-mediated type 1 diabetes mellitus. After prompt and adequate treatment of diabetic ketoacidosis/hyperosmolar hyperglycaemic state, she was discharged improved on multiple daily injections of insulin.